Imaginationen - Wardenga, Ute (Dialektik des Globalen. Kernbegriffe, 2019)
In the 18th century, the power of the imagination, which had previously been regarded as problematic, experienced a radical upsurge in esteem. In the modern era, imagination has been viewed as an essential moment in processes of planning, designing, and organizing the world. The creative capacity to place things in relation to each other in time and space has since been considered a vital force in history.